The Routledge companion to Black women's cultural histories
1 online resource
Keywords: "In the social and cultural histories of women and feminism, Black women have long been overlooked or ignored. The Routledge Companion to Black Women's Cultural Histories is an impressive and comprehensive reference work for contemporary scholarship on the cultural histories of Black women across the diaspora spanning different eras from ancient times into the twenty-first century. Comprising over thirty chapters by a team of international contributors, the Companion is divided into five parts: A Fragmented Past, An Inclusive Future Contested Histories, Subversive Memories Gendered Lives, Racial Frameworks Cultural Shifts, Social Change, Black Identities, Feminist Formations Within these sections a diverse range of women, places and issues are explored including: The Queen of Sheba, Black Women in Early Modern European Art and Culture, Enslaved Muslim Women in the Antebellum United States, Sally Hemings, and Phillis Wheatley, Black women writers in Early 20th Century Paris, Black women, Civil Rights, South African Apartheid, and sexual violence and resistance in the United States in recent history. The Routledge Companion to Black Women's Cultural Histories is essential reading for students and researchers in Gender Studies, History, Africana Studies and Cultural Studies"--